SCANNER OBJEK TIGA DIMENSI DENGAN LASER - Wiedjaja, Wiedjaja; Liawatimena, Suryadiputra (CommIT (Communication and Information Technology) Journal, 2008)
Article present the work and fuction of a tool which is able to scan an object reconstructed into a three-dimensionalobject. The object could be modified by computer software. Methodology were library and laboratory research methods. Fromthe experiment results, the scanning and reconstruction process of three-dimensional object could work well. The conclusionobtained is the optimum angle to scan the object is at an angle of 25o to 35o. While the average time needed to play the discis 50 seconds.Keywords: scanner, object, three-dimensional scanning, reconstruction